Jason and the golden fleece - Zeff, Claudia; Kelly, Alison Harvey, Gill Cartwright, Stephen Apollonius (Usborne London, 2003)
Series two of 'Usborne's Young Reading' books, which combines good stories with easy-reading text and illustrations, is for readers who are gaining confidence in reading alone